Immunology: antibodies to Chlamydia trachomatis in semen and relationship with parameters of male fertility - Eggert-Kruse, Waltraud; Buhlinger-Göpfarth, Nicola; Rohr, Gerhard; Probst, Stephan M.; Aufenanger, Johannes; Näher, Helmut; Runnebaum, Benno (Human reproduction, 1996)
To screen for infection with Chiamydia trachomatis in semen samples from asymptomatic men in couples consulting for infertility and to determine the relationship of seminal chiamydial antibodies with clinically relevant parameters of male fertility, 197 randomly chosen patients were enrolled in a prospective study. The median duration of infertility was 4 years (range 1-18). Screening for C.trachomatis and chlaniydial antibodies of the immunoglobulin (Ig) A and IgG classes was performed in ejaculates and, in parallel, endocervical material from the partners of the patients and serum samples from both partners were evaluated. A comprehensive examination of semen quality included sperm analyses, semen cultures, local antisperm antibody (ASA) testing, the determination of potential infection markers, and sperm-cervical mucus interaction testing in vitro (SCMIPT) and in vivo (post-coital testing). Chlamydial IgA antibodies were found in the semen samples of 18.8% (37/197) of the patients, while chlamydial IgG antibodies were found in 8.1% (16/197) of the patients. Screening for C.trachomatis was negative in all semen and cervical specimens. Only 5.5% of men remembered a past genital infection. Chiamydial antibodies (IgA/IgG) in semen were significantly correlated with chiamydial IgG antibod ies in serum samples (P<0.001). No marked relationship was found between the presence of seminal chlamydial antibodies and the major parameters of sperm analysis, semen cultures, local ASA and sperm penetration testing as an indicator of functional capacity. Seminal chlamydial antibodies were not significantly associated with potential infection or inflammation markers in aliquots of the same ejaculates. However, a significant relationship of chlamydial antibodies in patients' semen with past genital infections of their female partners was found with clinical relevance for a tubal infertility factor. The results indicate that in asymptomatic patients the presence of chlamydial antibody IgA or IgG in semen is not associated with reduced semen quality, potential seminal infection markers or impaired functional capacity as important determinants of male fertility; however, seminal chlamydial antibodies suggesting a previous sexually transmitted disease are signhlicantly related to a tubal infertility factor of female partners.
Gesehen am 18.11.2024